2014
DOI: 10.1016/j.pain.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Altered structure and function in the hippocampus and medial prefrontal cortex in patients with burning mouth syndrome

Abstract: Burning mouth syndrome (BMS) is a debilitating, idiopathic chronic pain condition. For many BMS patients, burning oral pain begins in late morning and becomes more intense throughout the day, peaking by late afternoon or evening. We investigated brain gray matter volume (GMV) with voxel-based morphometry (VBM), white matter fractional anisotropy (FA) with diffusion tensor imaging (DTI), and functional connectivity in resting state functional MRI (rsfMRI) in a tightly screened, homogeneous sample of 9 female, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 59 publications
9
135
0
2
Order By: Relevance
“…TMD is associated with a decrease in striatal dopaminergic uptake (Jaaskelainen et al 2001) and with changes in gray and white matter properties of corticolimbic regions (Younger et al 2010;Moayedi et al 2012). Moreover, patients suffering from burning mouth syndrome show structural differences in the hippocampus and mPFC, as well as increased functional connectivity between frontal and limbic regions as the pain increases (Khan et al 2014). Moreover, sustained pain from postoperative dental surgery is associated with higher cerebral blood flow in the thalamus, frontal regions, and sensorimotor cortex (Newberg et al 2011).…”
Section: Corticolimbic Signaling and Transition To Chronic Painmentioning
confidence: 99%
“…TMD is associated with a decrease in striatal dopaminergic uptake (Jaaskelainen et al 2001) and with changes in gray and white matter properties of corticolimbic regions (Younger et al 2010;Moayedi et al 2012). Moreover, patients suffering from burning mouth syndrome show structural differences in the hippocampus and mPFC, as well as increased functional connectivity between frontal and limbic regions as the pain increases (Khan et al 2014). Moreover, sustained pain from postoperative dental surgery is associated with higher cerebral blood flow in the thalamus, frontal regions, and sensorimotor cortex (Newberg et al 2011).…”
Section: Corticolimbic Signaling and Transition To Chronic Painmentioning
confidence: 99%
“…These neurotransmitters are also involved in humans and they affect depression due to close association of the brainstem raphe nuclei with dorso-caudal limbic system. In some previous studies, the authors (11,12) used transcranial ultrasonography of the brain parenchyma, thus revealing reduced raphe echogenicity in patients with major depressive disorder and, also, with suicidal tendencies. In the present study, hypoechogenicity of the midbrain raphe was found in BMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ovi neurotransmiteri također su uključeni kod ljudi i utječu na depresiju zbog bliske povezanosti nuclei raphe s dorzo-kaudalnim limbičkim sustavom. U nekim dosadašnjim istraživanjima autori su (11,12) pokazali, koristeći se transkranijalnim ultrazvukom moždanoga parenhima, smanjenu ehogenost nuclei raphe kod pacijenata s velikim depresivnim poremećajem i suicidalnim sklonostima. U ovom istraživanju također smo ustanovili hipoehogenosti nuclei raphe kod bolesnika sa SPU-om.…”
Section: Conflict Of Interestunclassified
“…However, it is unclear whether these alterations in GM volume acted as a predisposing factor or a secondary effect caused by disease-related conditions. Various types of chronic pain consist of another condition that is also frequently related to personality and mood changes of the patient, specifically anxiety and depression (Burgmer et al, 2009;Seminowicz et al, 2011;As-Sanie et al, 2012;Khan et al, 2014). VBM is a method of assessing brain GM volume that has previously been applied to various chronic pain conditions (Apkarian et al, 2004;Draganski et al, 2006;May, 2008;Younger et al, 2010;As-Sanie et al, 2012;Khan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%